Study On Acid Hydrolysis Conditions of Chaetomorpha Linum Green Seaweed to Application for Ethanol Production - Vo, Thanh Trung; Le, Nhu Hau; Nguyễn, Thanh Hằng (Old Journal, 2017)
Green seaweed Chaetomorpha linum has high carbohydrate content, therefore it is suitable for ethanol production. [cite: 8] In this study, C. linum was hydrolyzed by sulfuric acid. [cite: 9] This process has been investigated following factors, seaweed ratio 75-200 g/l, acid concentration 0-4 %v/v, temperature $90-130^{°}C$ and time 20- 80 minutes. [cite: 10] The optimal factors were determined as hydrolysis time of 54 minutes, temperature of $123^{°}C,$ acid concentration of 3,3 %v/v resulting in the hydrolysate 53.2 g/l of sugar which contained glucose of 32.1 g/l, galactose of 7.8 g/l and rhamnose of 12.6 g/l. [cite: 11] In conclusion, this hydrolysate contains a high glucose amount that is appropriate for yeast fermentation with 18.1 g/l ethanol production. [cite: 12]